The corporatization of Sabah electricity board : changes in the budgetary process / Rasid Mail - Mail, Rasid (2007)
Privatization is an important economic policy in Malaysia. Implemented for more than twenty years, its success and failure stories were responded to equivocally by the practitioners, policy makers, politicians, researchers, and the public at large. One of its critical success factors is the management of organizational change processes. The organizational change process is a complex phenomenon. In the process of privatization it involves the transformation of organization templates, from its public sector sphere to a commercial ethos. It is politically, psychologically, and socially intense, and results from coercive mechanisms as well as normative and mimetic processes. However, the organizational change process in a privatization context is also a ‘taken for granted’ phenomenon. One of the areas involved in the process is changes in accounting practice, and this research is concerning management accounting practice, focusing on the budgetary process. As commercial and managerial concepts are particular interests of the privatization policy, accounting practice changes to suit the new environment. It can respond to a new regulatory regime, the nature of the organizational transformation process, and strategic purposes. To an extent, the failure of a privatized organization to compete might be traced to the failure of its accounting practice to change. Thus, this research recognizes accounting’s potential to enhance organization visibility, to enhance organizational economic and social conceptualizations, and to facilitate behavior in an organizational social setting. In other words, accounting is not a neutral phenomenon, rather, it influences and is influenced by the organization’s social processes.